PENGARUH KUALITAS PELAYANAN TERHADAP NILAI PELANGGAN, KEPUASAN PELANGGAN SERTA IMPLIKASINYA TERHADAP LOYALITAS PELANGGAN (Survey pada Pelanggan Alfamart Di Kota Malang) - Saraswati, Dinastya (Jurnal Bisnis dan Manajemen, 2016)
This study aims to analyze and explain the influence of Quality of Service on Customer Value and Customer Satisfaction and Customer Loyalty. Analyze and explain the influence of the Customer Value Customer Satisfaction and Customer Loyalty. Analyze and explain the effect of Customer Satisfaction to Customer Loyalty. This study included an explanatory research. The number of samples in this study as many as 102. The sampling technique using Accidental Sampling. The technique of collecting data using questionnaires. Data were analyzed using path analysis. The results showed that service quality significantly influence Customer Value. Quality Services significantly influence customer satisfaction. Customer Value significantly influence customer satisfaction. Quality Services significantly influence Customer Loyalty. Customer Value significantly influence Customer Loyalty. Customer satisfaction significantly influence Customer Loyalty.